2019
DOI: 10.2147/dddt.s222296
|View full text |Cite
|
Sign up to set email alerts
|

<p>Paclitaxel alleviated sepsis-induced acute lung injury by activating MUC1 and suppressing TLR-4/NF-κB pathway</p>

Abstract: PurposeIt has been reported that approximately 40% of ALI (acute lung injury) incidence resulted from sepsis. Paclitaxel, as a classic anti-cancer drug, plays an important role in the regulation of inflammation. However, we do not know whether it has a protective effect against CLP (cecal ligation and puncture)-induced septic ALI. Our study aims to illuminate the mitigative effects of paclitaxel on sepsis-induced ALI and its relevant mechanisms.Materials and methodsThe survival rates and organ injuries were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…During the inflammatory process of ALI/ARDS, several signal transduction pathways such as nuclear factor kappa-B (NF-κB), mitogen-activated protein kinase (MAPK), nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing 3 (NLRP3), toll like receptors (TLRs), adrenergic receptors and JAK/STAT signaling pathways are involved [ [25] , [26] , [27] ]. Inhibition of NF-κB expression can inhibit the expression of inflammatory cytokines in the lungs, significantly reduce the inflammatory response in the lungs and improve the survival rate of lipopolysaccharide (LPS)-induced ALI mice [ 28 ]. In addition, the ablation of proteins such as NAMPT, Rip2 and Pfkfb3, which could activate the NF-κB signaling pathway, were found to prevent lung injury and inflammatory response in ischemia-reperfusion (I/R), LPS or cigarette smoke-induced ALI mice [ [29] , [30] , [31] , [32] ].…”
Section: Mechanisms Involved In Ali/ardsmentioning
confidence: 99%
“…During the inflammatory process of ALI/ARDS, several signal transduction pathways such as nuclear factor kappa-B (NF-κB), mitogen-activated protein kinase (MAPK), nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing 3 (NLRP3), toll like receptors (TLRs), adrenergic receptors and JAK/STAT signaling pathways are involved [ [25] , [26] , [27] ]. Inhibition of NF-κB expression can inhibit the expression of inflammatory cytokines in the lungs, significantly reduce the inflammatory response in the lungs and improve the survival rate of lipopolysaccharide (LPS)-induced ALI mice [ 28 ]. In addition, the ablation of proteins such as NAMPT, Rip2 and Pfkfb3, which could activate the NF-κB signaling pathway, were found to prevent lung injury and inflammatory response in ischemia-reperfusion (I/R), LPS or cigarette smoke-induced ALI mice [ [29] , [30] , [31] , [32] ].…”
Section: Mechanisms Involved In Ali/ardsmentioning
confidence: 99%
“…Accumulative studies have confirmed that the activation of NF-kB plays an important role in the occurrence and development of many critical illnesses, and the activation of NF-kB is also associated with a variety of inflammatory factors [ 22 ]. As a pleiotropic regulatory factor, NF-kB is at the core of inflammation and anti-inflammation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, in our study, we found that TLR4 levels were remarkedly decreased in serum, intestinal and lung tissues of rats with acute intestinal injury, which were ameliorated by emodin treatment. TLR4/NF-κB pathway has been reported to be closely related to acute intestinal/lung injury [2,25,26]. The NF-κB family consists of five members: P50, P52, p65/RelA, RelB and c-Rel.…”
Section: Discussionmentioning
confidence: 99%